2012
DOI: 10.1245/s10434-012-2296-4
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Versus Laparoscopic Resection of Large Adrenal Tumors

Abstract: Our study shows that the use of the robot could shorten operative time and decrease the rate of conversion to open for adrenal tumors larger than 5 cm. Based on our favorable experience, robotic adrenalectomy has become our preferred minimally invasive surgical approach for removing large adrenal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 28 publications
3
62
0
Order By: Relevance
“…In the Karabulut et al study, 28 cases were performed by two groups of staff (OR time = 142 ± 12 min) and 22 cases were done by one group of staff and one fellow (OR time: 201 ± 12 min); the difference in operative time was significantly different (p = 0.002) [18]. Agcaoglu et al also reported the presence of a fellow or a resident in almost 50% of surgeries in both groups, but this fact did not affect the operative time significantly [14].…”
Section: Critical Analysismentioning
confidence: 96%
See 3 more Smart Citations
“…In the Karabulut et al study, 28 cases were performed by two groups of staff (OR time = 142 ± 12 min) and 22 cases were done by one group of staff and one fellow (OR time: 201 ± 12 min); the difference in operative time was significantly different (p = 0.002) [18]. Agcaoglu et al also reported the presence of a fellow or a resident in almost 50% of surgeries in both groups, but this fact did not affect the operative time significantly [14].…”
Section: Critical Analysismentioning
confidence: 96%
“…The other significant outcome in favor of robotic surgery was the lower estimated blood loss, with a difference between groups reaching statistical significance (p = 0.001); seven of the nine studies reported less bleeding for robotics [14], [15], [16], [17], [18] and [19]. However, the detected difference of about 25 ml is not clinically relevant.…”
Section: Critical Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…Most of these studies have been retrospective observational comparative studies, 13,14,[16][17][18][19][20][21][22][23][24]26 and only one of them was a randomized controlled trial. 15 One of the first series comparing LA with robotic adrenalectomy was by Morino et al who evaluated outcomes in 10 patients who underwent laparoscopic and robotic adrenalectomy.…”
Section: Ra Vs Lamentioning
confidence: 99%